Analisis Penerapan Quizizz pada Materi Kenampakan Alam dan Keberagaman Sosial Budaya di Sekolah Dasar - Nur Qorimah, Esti; Aulia Saputri, Davina; Ahmad Firmansyah, Dio; Anasta Cahyani, Dela (Scholarly Journal of Elementary School, 2025)
This study was conducted with the aim of analyzing the application of quizizz on natural appearance material and socio-cultural diversity in elementary schools. The method in this study uses a type of qualitative research with descriptive analysis. The implementation subjects in this study were class V homeroom teachers of SD Negeri 1 Ketepung and grade V students of SD Negeri 1 Ketepung. The results in this study include: 1) In doing practice questions students still have difficulties because students tend to be bored with the method; 2) In explaining the material, teachers often use YouTube media and the quizizz application in the learning evaluation process because using quizizz is able to make students better understand and interested in the material of natural appearance and cultural diversity; 3) Teachers experience problems in accessing quizizz because the position of the school tends to be remote and internet access is limited. For this reason, it can be concluded that through quizizz, the material will be conveyed well to students and the level of student understanding is higher than using conventional methods.